(untitled) - Marschner, Horst (Amsterdam, 1995)
The product is very concise and interestihg for the study and understanding of plant nutrition. The book is very practical and presents good subjects and practices in agronomy
Phì nhiêu đất ứng dụng,Dinh dưỡng cây trồng,Thâm cứu dinh dưỡng cây trồng II,Thâm cứu dinh dưỡng cây trồng,Dinh dưỡng cây trồng
Keywords: Plants,Plants,Cây trồng; Nutrition,Effect of minerals on,Dinh dưỡng